Respiratory and bloodstream coinfections and antimicrobial use in hospitalised patients with moderate to severe COVID-19: An Australian retrospective cohort study - Laura Frederiksen; Shradha Subedi; Keat Choong; James Anderson; Timothy Baird (PLoS ONE, 2026)
Background COVID-19 remains a leading infectious cause of death and hospitalisation globally. Coinfections with SARS-CoV-2 and other respiratory pathogens may result in more severe illness, however the prevalence of coinfection in Australia is unknown. Aims This Australian study aimed to determine the prevalence and microbiology of respiratory and bloodstream coinfections, antimicrobial use, and outcomes in hospitalised patients with moderate to severe COVID-19. Methods This was a retrospective cohort study of adult patients with moderate to severe COVID-19, admitted at the Sunshine Coast University Hospital from February to July 2022. Data regarding patient characteristics, comorbidities, microbiological results, hospital length of stay, intensive care unit admission, and mortality were compared between the coinfection and no-coinfection groups. Logistic regression analysis was performed to identify factors associated with coinfection. Results Coinfection was documented in 23 (12%) of the 190 patients admitted with moderate-severe COVID-19. Bacterial infections were the most common (54% of coinfection episodes), followed by fungal (32%), and viral (14%). Antibiotics were prescribed for 74% of patients, for a median duration of 6 days (IQR 4–8 days). Patients with coinfection had a median length of stay of 9 days (IQR: 4–19.5) compared to 6 days in the no-coinfection group (IQR: 3–9; p = 0.047). There was no mortality difference between the two groups. Patients admitted to intensive care had higher odds of coinfection compared to patients not admitted to intensive care (OR 3.39, 95% CI 1.19–9.66, p = 0.02). Severe COVID-19 and Aboriginal and Torres Strait Islander descent were also associated with coinfection. The causal nature of these relationships requires further interrogation. Conclusions The prevalence of respiratory and bloodstream coinfection was low in our cohort of hospitalised COVID-19 patients. Despite non-standardised microbiological testing, antibiotic use was disproportionately high. Further work is required to define risk factors and improve diagnosis of COVID-19-associated coinfection, to better inform antimicrobial stewardship.